Race to Witch Mountain - Ponti, James; Lopez, Matt.; Bomback, Mark.; Fickman, Andy.; Walt Disney Pictures; Disney Enterprises (1996- ) (New York, NY : Disney Press, 2009)
Las Vegas cabdriver Jack Bruno gives two teenagers, Seth and Sara a ride. His world is about to change, since Seth and Sara are aliens who crashed landed their spaceship. They need help recovering their spaceship so they may return home.
Contains 8 pages of pictures from the film.
"Based on the new movie from Walt Disney Pictures." -- Cover.
Keywords: Aliens -- Juvenile fiction; Nevada -- Juvenile fiction; Fantasy fiction; Adventure stories